2010
DOI: 10.1136/bcr.08.2010.3262
|View full text |Cite
|
Sign up to set email alerts
|

Nevoid malignant melanoma in an albino woman

Abstract: SummaryAlbinism is a disorder of hypopigmentation affecting the skin, hair and eyes. Ultraviolet light induced cutaneous tumours are common in patients with albinism due to reduced or absent protection from melanin, with squamous cell carcinoma being the most common. Although nonmelanomatous skin cancers are more frequent in patients with albinism, dysplastic nevi and melanoma present a greater diagnostic challenge in this group because of their hypopigmented appearance. Here the authors report a case of nevoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Decreased melanin production results in individuals with OCA having a heightened sensitivity to ultraviolet radiation (UVR), predisposing them to skin cancers such as squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) (Lookingbill, Lookingbill, & Leppard, ; Okoro, ). The occurrence of cutaneous melanoma (CM) is rare in OCA populations, but when it does occur, CM is predominantly of the amelanotic subtype (Binesh, Akhavan, & Navabii, ; Dargent, Lespagnard, Heenen, & Verhest, ; Ihn et al, ; Levine, Ronan, Shirali, Gupta, & Karakousis, ) and patients rarely develop multiple primary melanomas (MPMs) (De Summa et al, ). Genome‐wide association studies (GWAS) have identified several loci associated with CM, including the OCA genes TYR (rs1393350; p = 2.4 × 10 −25 ) , OCA2 (rs4778138; p = 2.2 × 10 −11 ) and SLC45A2 (rs250417; p = 2.3 × 10 −12 ) (Law et al, ), hypothesized to be mediated through their roles in pigmentation.…”
Section: Heterozygous Germline Variants In Oca Genes: Variants In Ocamentioning
confidence: 99%
“…Decreased melanin production results in individuals with OCA having a heightened sensitivity to ultraviolet radiation (UVR), predisposing them to skin cancers such as squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) (Lookingbill, Lookingbill, & Leppard, ; Okoro, ). The occurrence of cutaneous melanoma (CM) is rare in OCA populations, but when it does occur, CM is predominantly of the amelanotic subtype (Binesh, Akhavan, & Navabii, ; Dargent, Lespagnard, Heenen, & Verhest, ; Ihn et al, ; Levine, Ronan, Shirali, Gupta, & Karakousis, ) and patients rarely develop multiple primary melanomas (MPMs) (De Summa et al, ). Genome‐wide association studies (GWAS) have identified several loci associated with CM, including the OCA genes TYR (rs1393350; p = 2.4 × 10 −25 ) , OCA2 (rs4778138; p = 2.2 × 10 −11 ) and SLC45A2 (rs250417; p = 2.3 × 10 −12 ) (Law et al, ), hypothesized to be mediated through their roles in pigmentation.…”
Section: Heterozygous Germline Variants In Oca Genes: Variants In Ocamentioning
confidence: 99%
“…Underlying OCA is not known to alter the management of skin malignancies. This is evident from various case reports where nonmetastatic skin tumors were managed with wide local excision in patients with albinism [ 9 , 11 ]. Hence, each individual lesion was excised and submitted for histological assessment.…”
Section: Discussionmentioning
confidence: 99%